Perceived social support networks and prosocial outcomes among Latino youth - de Guzman, Maria Rosario T.; Jung, Eunju; Do, Anh (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
This study examines the perceived sources and types of social support among Latino adolescents in the US, and links between social support and prosocial tendencies. Latino adolescents (n=126) participated in the study. Respondents of higher generational status reported broader social support networks and a higher amount of overall social support compared to peers of lower generational status. Youth perceived the highest amount of social support from immediate family, followed by extended family, and lastly from non-kin individuals. Path analysis indicated that overall social support was directly and positively associated with altruistic prosocial tendencies, and directly and negatively associated with public prosocial tendencies. Social support was indirectly related to altruistic, public, dire and emotional prosocial tendencies variably mediated by empathy, perspective taking and self-efficacy.